Freudig in die Schlacht - Emotionen als Codes für die recta intentio im gerechten Krieg (8.- 10. Jahrhundert) - Foerster, Anne (Emotionen im Krieg - Krieg der Emotionen)

The Swineherd’s Wife who Scolded the King - Foerster, Anne (Women in Early Medieval England)

Eadburh of Wessex - Foerster, Anne (Women in Early Medieval England)

Seaxburh - Foerster, Anne (Women in Early Medieval England)

Transformation durch Vermittlung. Das Heilige in der Geschichte pädagogischen und literarischen Wirkens der Jesuiten in Lateinamerika - Freitag, Christine; Thiem, Annegret ((Un)verfügbar - Kulturen des Heiligen)

Struktur und Sonderbauten der Silberbergbaustädte des 16. Jahrhunderts. Zur Korrelation von Städtebau und Montanwesen (Potosí und das Erzgebirge) - Silvestri, Marco (Bergbau und Hausbau)

Quantum 2-SAT on low dimensional systems is $\mathsf{QMA}_1$-complete: Direct embeddings and black-box simulation - Rudolph, Dorian; Gharibian, Sevag; Nagaj, Daniel (arXiv:2401.02368)
Despite the fundamental role the Quantum Satisfiability (QSAT) problem has played in quantum complexity theory, a central question remains open: At which local dimension does the complexity of QSAT transition from "easy" to "hard"? Here, we study QSAT with each constraint acting on a $k$-dimensional and $l$-dimensional qudit pair, denoted $(k,l)$-QSAT. Our first main result shows that, surprisingly, QSAT on qubits can remain $\mathsf{QMA}_1$-hard, in that $(2,5)$-QSAT is $\mathsf{QMA}_1$-complete. In contrast, $2$-SAT on qubits is well-known to be poly-time solvable [Bravyi, 2006]. Our second main result proves that $(3,d)$-QSAT on the 1D line with $d\in O(1)$ is also $\mathsf{QMA}_1$-hard. Finally, we initiate the study of 1D $(2,d)$-QSAT by giving a frustration-free 1D Hamiltonian with a unique, entangled ground state. Our first result uses a direct embedding, combining a novel clock construction with the 2D circuit-to-Hamiltonian construction of [Gosset, Nagaj, 2013]. Of note is a new simplified and analytic proof for the latter (as opposed to a partially numeric proof in [GN13]). This exploits Unitary Labelled Graphs [Bausch, Cubitt, Ozols, 2017] together with a new "Nullspace Connection Lemma", allowing us to break low energy analyses into small patches of projectors, and to improve the soundness analysis of [GN13] from $Ω(1/T^6)$ to $Ω(1/T^2)$, for $T$ the number of gates. Our second result goes via black-box reduction: Given an arbitrary 1D Hamiltonian $H$ on $d'$-dimensional qudits, we show how to embed it into an effective null-space of a 1D $(3,d)$-QSAT instance, for $d\in O(1)$. Our approach may be viewed as a weaker notion of "simulation" (à la [Bravyi, Hastings 2017], [Cubitt, Montanaro, Piddock 2018]). As far as we are aware, this gives the first "black-box simulation"-based $\mathsf{QMA}_1$-hardness result, i.e. for frustration-free Hamiltonians.

Hilfst du mir, so hilfst du dir. Diplomatische Überzeugungsstrategien der Regentin Christine Charlotte von Ostfriesland gegenüber Kaiser Leopold I. im 17. Jahrhundert (erscheint 2024) - Becker, Rieke (Österreichische Zeitschrift für Geschichtswissenschaften. Themenband „New Diplomatic History“)
Keywords: New Diplomatic History; Neue Diplomatiegeschichte

Materialschonende Verarbeitung von Thermoplasten auf Wave-Schnecken - Schall, Christoph Wilhelm Theodor
Die Extrusion stellt das mengenmäßig dominante Verarbeitungsverfahren für thermoplastische Kunststoffe dar. Daher gibt es starke Bestrebungen in diesem Bereich hin zu einer höheren Wirtschaftlichkeit, welche beispielsweise durch höheren Massedurchsatz bei gleichbleibender Maschinengröße erreicht werden kann, oder aber auch im Hinblick auf eine Kreislaufwirtschaft die Bestrebung hin zu einer materialschonenden Verarbeitung. Beide Bestrebungen erfordern spezielle Schneckenkonzepte. Hierunter fallenWave- Schnecken, welche in beiden Bereichen ein vorteilhaftes Prozessverhalten aufzeigen sollen. Die Auslegung von Wave-Schnecken erfordert jedoch ein stärkeres Verständnis über das geometrieabhängige Prozessverhalten in der Extrusion. Im Rahmen der Dissertation werden zwei Themengebiete angegangen. Das erste Thema ist die Herleitung einer Methode zur Charakterisierung des Abbauverhaltens von Thermoplasten sowie die Nutzung der Charakterisierung als Vorhersagemodell. Das zweite Thema behandelt die Auslegung von Wave-Schnecken basierend auf numerischen Simulationen samt Validierung anhand von sieben Energy-Transfer-Schnecken im Vergleich zu drei konventionellen Schnecken. Hierbei werden unter anderem der Materialabbau, die thermische und die stoffliche Homogenität betrachtet, um ein umfassendes Bild über das Prozessverhalten der Schnecken zu schaffen. Die vorgestellten Untersuchungen dienen schlussendlich zu einer Bestätigung des vorteilhaften Prozessverhaltens von Wave-Schnecken.

COVID-19 in Female and Male Athletes: Symptoms, Clinical Findings, Outcome, and Prolonged Exercise Intolerance—A Prospective, Observational, Multicenter Cohort Study (CoSmo-S) - Widmann, Manuel; Gaidai, Roman; Schubert, Isabel; Grummt, Maximilian; Bensen, Lieselotte; Kerling, Arno; Quermann, Anne; Zacher, Jonas; Vollrath, Shirin; Bizjak, Daniel Alexander; Beckendorf, Claudia; Egger, Florian; et al. (Sports Medicine)
Abstract Background An infection with SARS-CoV-2 can lead to a variety of symptoms and complications, which can impair athletic activity. Objective We aimed to assess the clinical symptom patterns, diagnostic findings, and the extent of impairment in sport practice in a large cohort of athletes infected with SARS-CoV-2, both initially after infection and at follow-up. Additionally, we investigated whether baseline factors that may contribute to reduced exercise tolerance at follow-up can be identified. Methods In this prospective, observational, multicenter study, we recruited German COVID elite-athletes (cEAs, n = 444) and COVID non-elite athletes (cNEAs, n = 481) who tested positive for SARS-CoV-2 by PCR (polymerase chain reaction test). Athletes from the federal squad with no evidence of SARS-CoV-2 infection served as healthy controls (EAcon, n = 501). Questionnaires were used to assess load and duration of infectious symptoms, other complaints, exercise tolerance, and duration of training interruption at baseline and at follow-up 6 months after baseline. Diagnostic tests conducted at baseline included resting and exercise electrocardiogram (ECG), echocardiography, spirometry, and blood analyses. Results Most acute and infection-related symptoms and other complaints were more prevalent in cNEA than in cEAs. Compared to cEAs, EAcon had a low symptom load. In cNEAs, female athletes had a higher prevalence of complaints such as palpitations, dizziness, chest pain, myalgia, sleeping disturbances, mood swings, and concentration problems compared to male athletes ( p < 0.05). Until follow-up, leading symptoms were drop in performance, concentration problems, and dyspnea on exertion. Female athletes had significantly higher prevalence for symptoms until follow-up compared to male. Pathological findings in ECG, echocardiography, and spirometry, attributed to SARS-CoV-2 infection, were rare in infected athletes. Most athletes reported a training interruption between 2 and 4 weeks (cNEAs: 52.9%, cEAs: 52.4%), while more cNEAs (27.1%) compared to cEAs (5.1%) had a training interruption lasting more than 4 weeks ( p < 0.001). At follow-up, 13.8% of cNEAs and 9.9% of cEAs ( p = 0.24) reported their current exercise tolerance to be under 70% compared to pre-infection state. A persistent loss of exercise tolerance at follow-up was associated with persistent complaints at baseline, female sex, a longer break in training, and age > 38 years. Periodical dichotomization of the data set showed a higher prevalence of infectious symptoms such as cough, sore throat, and coryza in the second phase of the pandemic, while a number of neuropsychiatric symptoms as well as dyspnea on exertion were less frequent in this period. Conclusions Compared to recreational athletes, elite athletes seem to be at lower risk of being or remaining symptomatic after SARS-CoV-2 infection. It remains to be determined whether persistent complaints after SARS-CoV-2 infection without evidence of accompanying organ damage may have a negative impact on further health and career in athletes. Identifying risk factors for an extended recovery period such as female sex and ongoing neuropsychological symptoms could help to identify athletes, who may require a more cautious approach to rebuilding their training regimen. Trial Registration Number DRKS00023717; 06.15.2021—retrospectively registered.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Swing-up dynamics in quantum emitter cavity systems: Near ideal single photons and entangled photon pairs - Heinisch, Nils; Köcher, Nikolas; Bauch, David; Schumacher, Stefan (Physical Review Research)

BelgienNet – une plateforme pour l’accès aux langues et cultures de la Belgique - Huybrechts, Yves; Karaca, Resul (Synergies Pays germanophones)

Du Châtelet, Induction, and Newton’s Rules for Reasoning - Wells, Aaron (European Journal of Philosophy)
I examine Du Châtelet’s methodology for physics and metaphysics through the lens of her engagement with Newton’s Rules for Reasoning in Natural Philosophy. I first show that her early manuscript writings discuss and endorse these Rules. Then, I argue that her famous published account of hypotheses continues to invoke close analogues of Rules 3 and 4, despite various developments in her position. Once relevant experimental evidence and some basic constraints are met, it is legitimate to inductively generalize from observations; general hypotheses can thereafter be assumed as true until contrary experiments show otherwise. I conclude by arguing that this account of induction plays an essential role in her metaphysics, both in an argument for simple substances—which has an inductive premise—and in her attempt to distinguish acceptable and unacceptable metaphysical commitments.

Corrosion behaviour of self-piercing riveted joints with uncoated rivets in high nitrogen steel - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Production Engineering)

„Es nimmt der Raum gastfreundlich auf die Menge“. Theodor Hells Prolog zur Eröffnung des Dresdner Hoftheaters (1841) - Eke, Norbert Otto (Die Kunst der Theatereröffnung. Ästhetik und Sozialgeschichte von Bühnenprologen)

Qualitätsoffensive Ganztag - Praktische Methoden für den Weg zur guten Ganztagsbildung - Seitz, Simone; Hamacher, Catalina; Schieffer, Leonie; Bunte, Charline

Historisches Lernen in einer ‚(Geschichts-)Kultur der Digitalität‘? - Hartung, Olaf (Geschichtskulturen im digitalen Wandel?)

Geschichtskulturen im digitalen Wandel?

Het verhaal van Vlaanderen. Analyse van het mediaformat en het geschiedverhaal - Huybrechts, Yves; Schmitz, Sabine (bmgn — Low Countries Historical Review)

Fast Multiobjective Gradient Methods with Nesterov Acceleration via Inertial Gradient-Like Systems - Sonntag, Konstantin; Peitz, Sebastian (Journal of Optimization Theory and Applications)
We derive efficient algorithms to compute weakly Pareto optimal solutions for smooth, convex and unconstrained multiobjective optimization problems in general Hilbert spaces. To this end, we define a novel inertial gradient-like dynamical system in the multiobjective setting, which trajectories converge weakly to Pareto optimal solutions. Discretization of this system yields an inertial multiobjective algorithm which generates sequences that converge weakly to Pareto optimal solutions. We employ Nesterov acceleration to define an algorithm with an improved convergence rate compared to the plain multiobjective steepest descent method (Algorithm 1). A further improvement in terms of efficiency is achieved by avoiding the solution of a quadratic subproblem to compute a common step direction for all objective functions, which is usually required in first-order methods. Using a different discretization of our inertial gradient-like dynamical system, we obtain an accelerated multiobjective gradient method that does not require the solution of a subproblem in each step (Algorithm 2). While this algorithm does not converge in general, it yields good results on test problems while being faster than standard steepest descent.

Herstellung und Charakterisierung von Wood-Plastic-Composites (WPC) mit einer Matrix aus thermoplastischen Polyurethanen zur Erzeugung einer Holz-WPC-Verbundstruktur - Richters, Maximilian

Herausforderungen in der inklusiven Mädchenarbeit: Begleitforschung der „Inklusiven anonymen Zuflucht“ des Mädchenhaus Bielefeld e.V. - Richter, Susanne (Inklusiver Kinderschutz – Anforderungen, Herausforderungen, Perspektiven)

Der Imperativ der Biographisierung und die Ambivalenzen individueller Verantwortungszuschreibung - Dahmen, Stephan (Responsibilisierung)

Soziologie des Flitzers - Riedl, Lars (Kölner Zeitschrift für Soziologie und Sozialpsychologie)

"Das Berufsfeldpraktikum empfinde ich als nicht notwendig im Studium" - Evaluationsergebnisse zum Berufsfeldpraktikum aus Sicht von Lehramtsstudierenden - Meier, Jana; Vogelsang, Christoph; Rotärmel, Tanja (Das Berufsfeldpraktikum als Professionalisierungselement. Grundlagen, Konzepte, Beispiele für das Lehramtsstudium)

Pyroelectric influence on lithium niobate during the thermal transition for cryogenic integrated photonics - Thiele, Frederik; Hummel, Thomas; Lange, Nina Amelie; Dreher, Felix; Protte, Maximilian; Bruch, Felix vom; Lengeling, Sebastian; Herrmann, Harald; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Materials for Quantum Technology)
Abstract Lithium niobate has emerged as a promising platform for integrated quantum optics, enabling efficient generation, manipulation, and detection of quantum states of light. However, integrating single-photon detectors requires cryogenic operating temperatures, since the best performing detectors are based on narrow superconducting wires. While previous studies have demonstrated the operation of quantum light sources and electro-optic modulators in LiNbO 3 at cryogenic temperatures, the thermal transition between room temperature and cryogenic conditions introduces additional effects that can significantly influence device performance. In this paper, we investigate the generation of pyroelectric charges and their impact on the optical properties of lithium niobate waveguides when changing from room temperature to 25 K, and vice versa. We measure the generated pyroelectric charge flow and correlate this with fast changes in the birefringence acquired through the Sénarmont-method. Both electrical and optical influence of the pyroelectric effect occur predominantly at temperatures above 100 K.
Keywords: General Earth and Planetary Sciences; General Environmental Science

„4 THe BoYZ“ – Widmungen im Szene-Graffiti aus konstruktionsgrammatischer Perspektive. Die multimodale Relator-Konstruktion als grammatische Musterbildung im Horizont des Textes - Tophinke, Doris; Dübbert, Alexander (Konstruktionsgrammatik X. Textsorten und Textmuster als Konstruktionen?)

Perspectives of children and young people on their education as preparing for their future in the digital age: In-depth qualitative study in five European countries. - Eickelmann, Birgit; Barbovschi, M.; Holmarsdottir, H.B.; Parsanoglou, D.; Sisask, M.; Labusch, Amelie (Understanding the everyday digital lives of children and young people)

Untersuchung des Füllverhaltens holzfaserverstärkter Kunststoffe (WPC) mit hohen Füllstoffgehalten - Flachmann, Felix

Die Vorgeschichte der „sozialen Medien“. Über die Träume digitaler Vergemeinschaftung und freier Kommunikation - Schmitt, Martin (Soziale Medien – wie sie wurden, was sie sind)
Sind „soziale Medien“ überhaupt ein Thema für die Geschichtswissenschaft? Ja, denn die längere Geschichte der Digitalisierung, in der die „sozialen Medien“ einzuordnen sind, zählt bereits über 80 Jahre. Konrad Zuse und andere Ingenieure entwickelten seit 1941 die ersten Digitalcomputer, Unternehmer*innen, Wissenschaftler*innen und Staatenlenker*innen setzten diese seit den 1950er Jahren für ihre Zwecke ein, die Zivilgesellschaft adaptierte sie in den darauffolgenden Dekaden – all das prägte die sozio-digitale Landschaft der späteren „sozialen Medien“. Als unmittelbar „nach dem Boom“ etwa um 1970 zahlreiche Industriegesellschaften einen strukturellen Wandel in Wirtschaft, Gesellschaft und Politik durchlebten, war eine Antwort darauf die vermehrte Digitalisierung und Vernetzung. Daraus entwickelte sich die 1990er Jahre als markante Dekade von World Wide Web, Google und Chatdiensten. Die Entwicklung der „sozialen Medien“ ist also unter anderem in eine ökonomische und gesellschaftliche Entwicklung der Aufmerksamkeitsökonomie und in die längeren Veränderungen von Wirtschafts- und Gesellschaftsordnungen der Ausdifferenzierung und partiellen Individualisierung seit den 1960er Jahren einzuordnen. Dadurch lässt sich besser verstehen, welche Prämissen ihnen zugrunde lagen, welche Möglichkeitsräume und Probleme sich daraus ergaben und warum sie die heutige Öffentlichkeit in einer bestimmten Art und Weise dominieren – ohne sie jedoch zu determinieren.
Keywords: Digitalgeschichte; Soziale Medien; Technikgeschichte; World Wide Web; Digitalisierung

Alles geht? Die jüngste Geschichte der „sozialen Medien“. Zwischen Wirtschaft und Gemeinschaft - Schmitt, Martin (Soziale Medien – wie sie wurden, was sie sind)
Twitter ist jetzt X und befindet sich auf dem absteigenden Ast. Auf diesem Ast sitzt Facebook bereits seit längerem. Der Kurzvideodienst Vine, Vorgänger von TikTok, ist Geschichte. Und auch bei Google klingeln die Alarmglocken angesichts der „neuen“ Konkurrenz durch Microsoft und ChatGPT. Umso dringlicher wird also die Historisierung der „sozialen Medien“, das heißt, sie in ihren historischen Kontext einzuordnen und ihren Mythos zu entzaubern. Dabei wartet das Vorhaben mit einer doppelten Herausforderung auf: Erstens, dass es sich bei den Unternehmen der Branche und zweitens auch bei den dort gebildeten Gemeinschaften um recht flüchtige, wandelhaften Gestalten handelt. Scheitern und Wandel ist Teil der „sozialen Medien“ – und sei es nur in der schnellen Abfolge der Moden des „nächsten großen Dings“. Dementsprechend versucht dieser Beitrag mit einem systematischeren Ansatz als dem der gesellschaftlichen Selbstbeschreibung, die Entwicklung des sozio-digitalen Phänomens „soziale Medien“ in dessen Zeitkontext einzuordnen.
Keywords: Digitalgeschichte; Soziale Medien; Technikgeschichte; Wirtschaftsgeschichte; Digitalisierung; Twitter; Facebook; Meta

Simulationsgestützte Bestimmung und Optimierung der Mischgüte in der Einschneckenextrusion - Frank, Maximilian

Alexandra Treder (Universität Paderborn) rezensiert: Döll, Marion & Michalak, Magdalena (2023): Deutsch als Zweitsprache und inklusive Bildung. [Deutsch als Zweitsprache – Positionen, Perspektiven, Potenziale, Bd. 3]. Münster: Waxmann, 142 Seiten. ISBN 978-3-8309-4711-0. - Treder, Alexandra (Forschungsportal für Spracherwerb und Migration (daz-portal))

Children and young people’s ICT experiences in school education: Participatory research design to engage children and young people as experts in research - Labusch, Amelie; Eickelmann, Birgit; Casamassima, Gianna; Drossel, Kerstin; Gudmundsdottir, G.B.; Kazani, A.; Mifsud, L.; Symeonaki, M.; Teidla-Kunitsõn, G. (Understanding the everyday digital lives of children and young people)

From Swiss-cheese to discrete ferroelectric composites: assessing the ferroelectric butterfly shape in polarization loops - Myroshnychenko, Viktor; Mulavarickal Jose, Pious Mathews; Farheen, Henna; Ejaz, Shafaq; Brosseau, Christian; Förstner, Jens (Physica Scripta)
We explore the polarization hysteretic behaviour and field-dependent permittivity of ferroelectric-dielectric 2D materials formed by random dispersions of low permittivity inclusions in a ferroelectric matrix, using finite element simulations. We show how the degree of impenetrability of dielectric inclusions plays a substantial role in controlling the coercive field, remnant and saturation polarizations of the homogenized materials. The results highlight the significance of the degree of impenetrability of inclusion in tuning the effective polarization properties of such ferroelectric composites: coercive field drops significantly as percolation threshold is attained and remnant polarization decreases faster than a linear decay.
Keywords: tet_topic_ferro

Edge-Connectivity and Pairwise Disjoint Perfect Matchings in Regular Graphs - Ma, Yulai; Mattiolo, Davide; Steffen, Eckhard; Wolf, Isaak Hieronymus (Combinatorica)
For 0 ≤ t ≤ r let m(t, r) be the maximum number s such that every t-edge-connected r-graph has s pairwise disjoint perfect matchings. There are only a few values of m(t, r) known, for instance m(3, 3) = m(4, r) = 1, and m(t, r) ≤ r − 2 for all t = 5, and m(t, r) ≤ r − 3 if r is even. We prove that m(2l, r) ≤ 3l − 6 for every l ≥ 3 and r ≥ 2l.
Keywords: Computational Mathematics; Discrete Mathematics and Combinatorics

Time and Space Optimized Storage-based BIST under Multiple Voltages and Variations - Jafarzadeh, Hanieh; Klemme, Florian; Amrouch, Hussam; Hellebrand, Sybille; Wunderlich, Hans-Joachim (European Test Symposium, The Hague, Netherlands, May 20-24, 2024)

Vmin Testing under Variations: Defect vs. Fault Coverage - Jafarzadeh, Hanieh; Klemme, Florian; Amrouch, Hussam; Hellebrand, Sybille; Wunderlich, Hans-Joachim (IEEE Latin American Test Symposium (LATS), Maceió, Brazil, April 9-12, 2024)

Functional Safety and Reliability of Interconnects throughout the Silicon Life Cycle - Hellebrand, Sybille; Sadeghi-Kohan, Somayeh; Wunderlich, Hans-Joachim (International Symposium of EDA (ISEDA), Xi'an, China, May 10-13, 2024)

Involvement of domain experts in the AI training does not affect adherence – An AutoML study - Lebedeva, Anastasia; Protte, Marius; van Straaten, Dirk; Fahr, René (Advances in Information and Communication)

Robust Test of Small Delay Faults under PVT-Variations - Wunderlich, Hans-Joachim; Jafarzadeh, Hanieh; Hellebrand, Sybille (International Symposium of EDA (ISEDA), Xi’an, China, May 10-13, 2024)

Modeling Crosstalk-induced Interconnect Delay with Polynomial Regression - Stiballe, Alisa; Reimer, Jan Dennis; Sadeghi-Kohan, Somayeh; Hellebrand, Sybille

Decomposing large unitaries into multimode devices of arbitrary size - Arends, Christian; Wolf, Lasse Lennart; Meinecke, Jasmin; Barkhofen, Sonja; Weich, Tobias; Bartley, Tim (Physical Review Research)
Keywords: General Physics and Astronomy

TS-SEP: Joint Diarization and Separation Conditioned on Estimated Speaker Embeddings - Boeddeker, Christoph; Subramanian, Aswin Shanmugam; Wichern, Gordon; Haeb-Umbach, Reinhold; Le Roux, Jonathan (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Keywords: Electrical and Electronic Engineering; Acoustics and Ultrasonics; Computer Science (miscellaneous); Computational Mathematics

Systematik zur musterbasierten Transformation von Wertschöpfungssystemen für Smart Services - Reinhold, Jannik

Eine Methode zur Unterstützung von Entscheidungen bei der Entwicklung modularer Leichtbauprodukte - Yang, X.

Digitale Plattformen und Ökosysteme im B2B-Bereich - Fallstudien, Ansätze, Technologien und Tools
Das Herausgeberwerk präsentiert aktuelle Forschungsergebnisse und praktische Erkenntnisse aus dem Bereich von digitalen Plattformen und Ökosystemen im Business-to-Business-Kontext. Dabei liegt der Schwerpunkt auf empirischen und konzeptionellen Beiträgen. Neben Grundlagen, Enablern und Fallstudien werden ebenso mögliche Vorgehensweisen zur Entwicklung von Plattformen behandelt. Praktikerinnen und Praktiker aus den Bereichen Management, Strategische Planung und Business Development erhalten Impulse, um Digitale Plattformen und Ökosysteme erfolgreich voranzutreiben und so Potenziale innerhalb ihres Unternehmens zu realisieren. Forschende, Lehrende und Studierende aus den Bereichen Digitale Plattformen und Ökosysteme aus dem Business-to-Business-Kontext dienen die Beiträge als Anregung für intensive Diskussionen.

Das Schreiben im Geschichtsunterricht der Sekundarstufe I unter Berücksichtigung der Bedingungen der Migrationsgesellschaft - Altun, Tülay; Günther, Katrin (Mehrsprachigkeit in der Schule. Sprachbildung im und durch Sachunterricht)

Herstellung und Charakterisierung von Wood-Plastic-Composites (WPC) mit einer Matrix aus thermoplastischen Polyurethanen zur Erzeugung einer Holz-WPC-Verbundstruktur - Richters, Maximilian

Ein Beitrag zur Erarbeitung von Fertigungsrichtlinien für das Kunststoff Freiformen - Hirsch, Andre

Materialschonende Verarbeitung von Thermoplasten auf Wave-Schnecken - Schall, Christoph Wilhelm Theodor

Experimentelle und simulative Analyse der Mischwirkung in Einschneckenextrudern - Schadomsky, Michael

Doing language im Deutschunterricht. Eine Analyse sprachbezogener Adressierungen in diskursiver Praxis - Büttner, Denise
Die Studie leistet einen empirisch-rekonstruktiven Beitrag zu einer machtkritisch ausgerichteten Fachdidaktik. Sie fokussiert den Deutschunterricht und die darin stattfindenden Interaktionen als diskursive Praxis, in der ein spezifisches Wissen in, über und angesichts von Sprache relevant gemacht wird. Für Subjektivierung ist jenes Wissen hochgradig wirkmächtig und bleibt den Akteur*innen im Prozess der schulischen Enkulturation doch größtenteils unbewusst. Darin liegt ein hohes Potential für die institutionelle (Re-)Produktion von Linguizismus.Vor diesem Hintergrund eröffnet die Studie einen Blick auf sprachbezogene Adressierungen, die in charakteristischer Weise vom Fach selbst ausgehen. Sie werden in (fach)didaktischen und pädagogischen Programmatiken breit kommuniziert und zeichnen sich bis auf die Ebene unterrichtlicher Praktiken ab. Um das Zusammenspiel von fachspezifischer Adressierung und Praktiken des ‚doing language‘ möglichst eng aufeinander beziehen und in rekonstruktionslogisch plausibilisierte Zusammenhänge bringen zu können, liegt der Arbeit ein wissenssoziologisch-diskursanalytischer Ansatz zugrunde.
Keywords: Diskursanalyse; Machtkritik; Sprache und Bildung; Rekonstruktive Unterrichtsforschung; Subjektivierung; Fachdidaktik

Optimization of the Downlink Spectral- and Energy-Efficiency of RIS-aided Multi-user URLLC MIMO Systems - Soleymani, Mohammad; Santamaria, Ignacio; Jorswieck, Eduard; Schober, Robert; Hanzo, Lajos (arXiv:2402.16434)
Modern wireless communication systems are expected to provide improved latency and reliability. To meet these expectations, a short packet length is needed, which makes the first-order Shannon rate an inaccurate performance metric for such communication systems. A more accurate approximation of the achievable rates of finite-block-length (FBL) coding regimes is known as the normal approximation (NA). It is therefore of substantial interest to study the optimization of the FBL rate in multi-user multiple-input multiple-output (MIMO) systems, in which each user may transmit and/or receive multiple data streams. Hence, we formulate a general optimization problem for improving the spectral and energy efficiency of multi-user MIMO-aided ultra-reliable low-latency communication (URLLC) systems, which are assisted by reconfigurable intelligent surfaces (RISs). We show that a RIS is capable of substantially improving the performance of multi-user MIMO-aided URLLC systems. Moreover, the benefits of RIS increase as the packet length and/or the tolerable bit error rate are reduced. This reveals that RISs can be even more beneficial in URLLC systems for improving the FBL rates than in conventional systems approaching Shannon rates.

Maximization of Minimum Rate in MIMO OFDM RIS-Assisted Broadcast Channels - Soleymani, Mohammad; Santamaria, Ignacio; Sezgin, Aydin; Jorswieck, Eduard (2023 IEEE 9th International Workshop on Computational Advances in Multi-Sensor Adaptive Processing (CAMSAP))

NOMA-Based Improper Signaling for MIMO STAR-RIS-Assisted Broadcast Channels with Hardware Impairments - Soleymani, Mohammad; Santamaria, Ignacio; Jorswieck, Eduard (GLOBECOM 2023 - 2023 IEEE Global Communications Conference)

Insights and Challenges of Co-Simulation-based Optimal Pulse Pattern Evaluation for Electric Drives - Hölsch, Lukas; Brosch, Anian; Steckel, Richard; Braun, Tristan; Wendel, Sebastian; Böcker, Joachim; Wallscheid, Oliver (IEEE Transactions on Energy Conversion)
Keywords: Electrical and Electronic Engineering; Energy Engineering and Power Technology

Rademacher Complexity Regularization for Correlation-Based Multiview Representation Learning - Kuschel, Maurice; Hasija, Tanuj; Marrinan, Timothy (ICASSP 2024 - 2024 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

A critical exponent in a quasilinear Keller–Segel system with arbitrarily fast decaying diffusivities accounting for volume-filling effects - Stinner, Christian; Winkler, Michael (Journal of Evolution Equations)
Abstract The quasilinear Keller–Segel system $$\begin{aligned} \left\{ \begin{array}{l} u_t=\nabla \cdot (D(u)\nabla u) - \nabla \cdot (S(u)\nabla v), \\ v_t=\Delta v-v+u, \end{array}\right. \end{aligned}$$ u t = ∇ · ( D ( u ) ∇ u ) - ∇ · ( S ( u ) ∇ v ) , v t = Δ v - v + u , endowed with homogeneous Neumann boundary conditions is considered in a bounded domain $$\Omega \subset {\mathbb {R}}^n$$ Ω ⊂ R n , $$n \ge 3$$ n ≥ 3 , with smooth boundary for sufficiently regular functions D and S satisfying $$D>0$$ D > 0 on $$[0,\infty )$$ [ 0 , ∞ ) , $$S>0$$ S > 0 on $$(0,\infty )$$ ( 0 , ∞ ) and $$S(0)=0$$ S ( 0 ) = 0 . On the one hand, it is shown that if $$\frac{S}{D}$$ S D satisfies the subcritical growth condition $$\begin{aligned} \frac{S(s)}{D(s)} \le C s^\alpha \qquad \text{ for } \text{ all } s\ge 1 \qquad \text{ with } \text{ some } \alpha < \frac{2}{n} \end{aligned}$$ S ( s ) D ( s ) ≤ C s α for all s ≥ 1 with some α < 2 n and $$C>0$$ C > 0 , then for any sufficiently regular initial data there exists a global weak energy solution such that $${ \mathrm{{ess}}} \sup _{t>0} \Vert u(t) \Vert _{L^p(\Omega )}<\infty $$ ess sup t > 0 ‖ u ( t ) ‖ L p ( Ω ) < ∞ for some $$p > \frac{2n}{n+2}$$ p > 2 n n + 2 . On the other hand, if $$\frac{S}{D}$$ S D satisfies the supercritical growth condition $$\begin{aligned} \frac{S(s)}{D(s)} \ge c s^\alpha \qquad \text{ for } \text{ all } s\ge 1 \qquad \text{ with } \text{ some } \alpha > \frac{2}{n} \end{aligned}$$ S ( s ) D ( s ) ≥ c s α for all s ≥ 1 with some α > 2 n and $$c>0$$ c > 0 , then the nonexistence of a global weak energy solution having the boundedness property stated above is shown for some initial data in the radial setting. This establishes some criticality of the value $$\alpha = \frac{2}{n}$$ α = 2 n for $$n \ge 3$$ n ≥ 3 , without any additional assumption on the behavior of D ( s ) as $$s \rightarrow \infty $$ s → ∞ , in particular without requiring any algebraic lower bound for D . When applied to the Keller–Segel system with volume-filling effect for probability distribution functions of the type $$Q(s) = \exp (-s^\beta )$$ Q ( s ) = exp ( - s β ) , $$s \ge 0$$ s ≥ 0 , for global solvability the exponent $$\beta = \frac{n-2}{n}$$ β = n - 2 n is seen to be critical.
Keywords: Mathematics (miscellaneous)

On the Potential of Multi-objective Automated Algorithm Configuration on Multi-modal Multi-objective Optimisation Problems - Preuß, Oliver Ludger; Rook, Jeroen; Trautmann, Heike (Applications of Evolutionary Computation)

Konzepte sprachlicher Bildung im Fachunterricht – Gemeinsamkeiten und Unterschiede - Böttger, Lydia; Mischendahl, Anne; Niederhaus, Constanze (Mehrsprachigkeit in der Schule: Sprachbildung im und durch Sachunterricht)

pyfds 0.3.1 - modular field simulation tool - Claes, Leander; Webersen, Manuel

Zwischen Beutesuche und politischen Ambitionen. Die Normannen an Rhein und Maas zwischen 880 und 892 - Kamp, Hermann (Zeitschrift des Aachener Geschichtsvereins)

‚Schelmische‘ Post-DDR-Romane: Ingo Schulzes „Peter Holtz“ und Lea Streisands „Hufeland, Ecke Bötzow“ - Elit, Stefan (‚Topographisches‘ Schreiben: Lea Streisand, Paderborn, Wintersemester 2022/2023)

Characterizing Microheterogeneity in Liquid Mixtures via Local Density Fluctuations - Lass, Michael; Kenter, Tobias; Plessl, Christian; Brehm, Martin (Entropy)
We present a novel approach to characterize and quantify microheterogeneity and microphase separation in computer simulations of complex liquid mixtures. Our post-processing method is based on local density fluctuations of the different constituents in sampling spheres of varying size. It can be easily applied to both molecular dynamics (MD) and Monte Carlo (MC) simulations, including periodic boundary conditions. Multidimensional correlation of the density distributions yields a clear picture of the domain formation due to the subtle balance of different interactions. We apply our approach to the example of force field molecular dynamics simulations of imidazolium-based ionic liquids with different side chain lengths at different temperatures, namely 1-ethyl-3-methylimidazolium chloride, 1-hexyl-3-methylimidazolium chloride, and 1-decyl-3-methylimidazolium chloride, which are known to form distinct liquid domains. We put the results into the context of existing microheterogeneity analyses and demonstrate the advantages and sensitivity of our novel method. Furthermore, we show how to estimate the configuration entropy from our analysis, and we investigate voids in the system. The analysis has been implemented into our program package TRAVIS and is thus available as free software.

'Topographisches‘ Schreiben: Lea Streisand. Paderborn Wintersemester 2022/23

Klopstocks lyrisches Spätwerk. Perspektivwechsel und Blickerweiterungen - Elit, Stefan („Wer wird nicht einen Klopstock loben?“ Friedrich Gottlieb Klopstocks poetische Innovationen und ihre produktive Rezeption)

‚Topographisches‘ Schreiben. Lea Streisand, Paderborn Wintersemester 2022/23: Die 41. Gastdozentur für Schriftstellerinnen und Schriftsteller. Zur Einführung. - Eke, Norbert (‚Topographisches‘ Schreiben: Lea Streisand – Paderborn Wintersemester 2022/23)

Sich selbst erzählen. Lea Streisands autofiktionales Erzählen. - Eke, Norbert (‚Topographisches‘ Schreiben: Lea Streisand – Paderborn Wintersemester 2022/23)

Digitale Plattformen im industriellen Mittelstand

Digitale Plattformen im industriellen Mittelstand

Scalable quantum detector tomography by high-performance computing - Schapeler, Timon; Schade, Robert; Lass, Michael; Plessl, Christian; Bartley, Tim (arXiv:2404.02844)
At large scales, quantum systems may become advantageous over their classical counterparts at performing certain tasks. Developing tools to analyse these systems at the relevant scales, in a manner consistent with quantum mechanics, is therefore critical to benchmarking performance and characterising their operation. While classical computational approaches cannot perform like-for-like computations of quantum systems beyond a certain scale, classical high-performance computing (HPC) may nevertheless be useful for precisely these characterisation and certification tasks. By developing open-source customised algorithms using high-performance computing, we perform quantum tomography on a megascale quantum photonic detector covering a Hilbert space of $10^6$. This requires finding $10^8$ elements of the matrix corresponding to the positive operator valued measure (POVM), the quantum description of the detector, and is achieved in minutes of computation time. Moreover, by exploiting the structure of the problem, we achieve highly efficient parallel scaling, paving the way for quantum objects up to a system size of $10^{12}$ elements to be reconstructed using this method. In general, this shows that a consistent quantum mechanical description of quantum phenomena is applicable at everyday scales. More concretely, this enables the reconstruction of large-scale quantum sources, processes and detectors used in computation and sampling tasks, which may be necessary to prove their nonclassical character or quantum computational advantage.

Asymptotic behavior of solutions to the extension problem for the fractional Laplacian on noncompact symmetric spaces - Papageorgiou, Efthymia (Journal of Evolution Equations)
Abstract This work deals with the extension problem for the fractional Laplacian on Riemannian symmetric spaces G / K of noncompact type and of general rank, which gives rise to a family of convolution operators, including the Poisson operator. More precisely, motivated by Euclidean results for the Poisson semigroup, we study the long-time asymptotic behavior of solutions to the extension problem for $$L^1$$ L 1 initial data. In the case of the Laplace–Beltrami operator, we show that if the initial data are bi- K -invariant, then the solution to the extension problem behaves asymptotically as the mass times the fundamental solution, but this convergence may break down in the non-bi- K -invariant case. In the second part, we investigate the long-time asymptotic behavior of the extension problem associated with the so-called distinguished Laplacian on G / K . In this case, we observe phenomena which are similar to the Euclidean setting for the Poisson semigroup, such as $$L^1$$ L 1 asymptotic convergence without the assumption of bi- K -invariance.
Keywords: Mathematics (miscellaneous)

Belgischer Symbolismus zum Be/Greifen nah. Museumskoffer zum Werk von Léon Spilliaert und George Minne.
Der belgische Symbolismus wurde in den letzten Jahrzehnten neu entdeckt. Während Künstler wie Léon Spilliaert und George Minne lange ein Geheimtipp waren, ziehen sie nun ein großes Publikum in ihren Bann. Dennoch gelten viele Werke dieser Kunstströmung bis heute aufgrund der sie prägenden anspruchsvollen Formensprache, verborgenen Bedeutungen und mystischen Visionen als ebenso anziehend wie unergründlich. Die hier vorgestellten siebzehn Museumskoffer bieten vielfältige Zugänge, sie in ihrem kulturellen und kunsthistorischen Kontext zu entdecken und zu verstehen: Sie machen kulturelles Lernen zu einem ganzheitlichen Erlebnis und öffnen Türen zu neuen Welten. Ergänzend stellt der Katalog Texte zum Medium ‚Museumskoffer‘, zum belgischen Symbolismus und weiteres relevantes Informationsmaterial zur Verfügung.
Keywords: Belgischer Symbolismus; Museumskoffer; León Spilliaert; George Minne

31 Sprachbildung im berufsbezogenen Mathematikunterricht. - Prediger, Susanne; Wessel, Lena (Berufs-und Fachsprache Deutsch in Wissenschaft und Praxis)

Implementation of Different Communication Structures for a Rocket Chip Based RISC-V Grid of Processing Cells - Luchterhandt, Lars; Nellius, Tom; Beck, Robert; Dömer, Rainer; Kneuper, Pascal; Müller, Wolfgang; Sadiye, Babak (MBMV 2024 - 27. Workshop Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen“)
RISC-V has received worldwide acceptance in the industry and by the academic community. As of today, multiple RISC-V applications and variants are under investigation for embedded IoT systems, from resource-limited single-core processors up to multi-core systems for High-Performance Computing (HPC). Recently, the Grid of Processing Cells (GPC) platform has been proposed as a scalable parallel grid-oriented network of processor cores with local memories. This paper describes a prototype design of the GPC platform for hardware implementation at Register-Transfer Level (RTL) based on modified RISC-V Rocket processors with scratchpad memories. It introduces a scalable Chisel-based implementation of the modified Rocket cores with RTL generation and a functional test using Verilator simulation. This work also includes the adaptation of the Chipyard software toolchain to extend the compiler to multi-core grids with different local address spaces.

A Scalable RISC-V Hardware Platform for Intelligent Sensor Processing - Palomero Bernardo, Paul; Schmid, Patrick; Bringmann, Oliver; Iftekhar, Mohammed; Sadiye, Babak; Müller, Wolfgang; Koch, Andreas; Jentsch, Eyck; Sauer, Axel; Feldner, Ingo; Ecker, Wolfgang (DATE 24 - Design Automation and Test in Europe)

„Wir wollen mitreden!“ – Entwicklung und Validierung von Skalen zur Erfassung motivationaler Regulation bei der Teilnahme an Befragungen zur Evaluation des Studiums (SMR-Eval) - Koppenborg, Markus; Klingsieck, Katrin B. (Zeitschrift für Pädagogische Psychologie)
Zusammenfassung: Für die Evaluation und Qualitätsentwicklung von Studium und Lehre werden häufig quantitative Befragungen von Studenten eingesetzt. Jedoch ist häufig unklar, aus welcher Motivation Studenten an den Befragungen teilnehmen und inwieweit unterschiedliche motivationale Regulationsstile mit dem Antwortverhalten im Fragebogen zusammenhängen. Ausgehend von der Selbstbestimmungstheorie der Motivation nach Deci und Ryan stellt der Beitrag die Entwicklung der Skalen zur motivationalen Regulation bei Befragungen zur Evaluation (SMR-Eval) vor. Studie 1 zeigt die fünffaktorielle Struktur des Instruments. Studie 2 weist auf eine starke Messinvarianz bezüglich Geschlecht, Abschlussziel und Fakultät hin. Korrelationen mit Drittvariablen belegen die konvergente Validität der fünf Subskalen. In Studie 3 werden latente Profilanalysen über die fünf Regulationsstile berechnet. Die Ergebnisse zeigen vier Profile, welche sich inhaltlich plausibel im Antwortverhalten der Befragten unterscheiden und damit Hinweise auf die Kriteriumsvalidität der Skalen geben. Diskutiert werden theoretische und praktische Implikationen für Evaluationsvorhaben an Hochschulen sowie Übertragungsmöglichkeiten auf andere Evaluationsgegenstände.
Keywords: Developmental and Educational Psychology

The association between dairy intake in adolescents with inflammation and risk markers of type 2 diabetes during young adulthood – results of the DONALD study - Hohoff, E; Jankovic, N; Perrar, I; Schnermann, ME; Herder, C; Nöthlings, U; Libuda, Lars; Alexy, U (Public Health Nutrition)
ABSTRACT OBJECTIVE: The aim of this analysis was to investigate whether habitual intake of total dairy (TD) or different dairy types (liquid, solid, fermented, not-fermented, low-fat, high-fat, low-sugar and high-sugar dairy) during adolescence is associated with biomarkers of low-grade inflammation as well as risk factors of type 2 diabetes in young adulthood. DESIGN: Multivariable linear regression analyses were used to investigate prospective associations between estimated TD intake as well as intake of different types of dairy and a pro-inflammatory score, based on hsCRP, IL-6, IL-18, leptin and adiponectin, and insulin resistance assessed as HOMA2-IR in an open cohort study. SETTING: Dortmund, Germany PARTICIPANTS: Data from participants (n=375) of the DOrtmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study were included, for whom at least two 3-day weighed dietary records during adolescence (median age: 11 years) and one blood sample in young adulthood (>18 years) were available. RESULTS: There was no statistically significant association between TD intake or intake of any dairy type and the pro-inflammatory score (all p>0.05). TD intake as well as each dairy type intake and insulin resistance also showed no association (all p>0.05). CONCLUSIONS: The habitual intake of dairy or individual types of dairy during adolescence does not seem to have a major impact on low-grade systemic inflammation and insulin resistance in the long term. There was no indication regarding a restriction of dairy intake for healthy children and adolescents in terms of diabetes risk reduction.
Keywords: Public Health; Environmental and Occupational Health; Nutrition and Dietetics; Medicine (miscellaneous)

Geodesic Interpolation of Frame-Wise Speaker Embeddings for the Diarization of Meeting Scenarios - Cord-Landwehr, Tobias; Boeddeker, Christoph; Zorilă, Cătălin; Doddipatla, Rama; Haeb-Umbach, Reinhold (ICASSP 2024 - 2024 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Noctua 2 Supercomputer - Bauer, Carsten; Kenter, Tobias; Lass, Michael; Mazur, Lukas; Meyer, Marius; Nitsche, Holger; Riebler, Heinrich; Schade, Robert; Schwarz, Michael; Winnwa, Nils; Wiens, Alex; Wu, Xin; et al. (Journal of large-scale research facilities)
Noctua 2 is a supercomputer operated at the Paderborn Center for Parallel Computing (PC2) at Paderborn University in Germany. Noctua 2 was inaugurated in 2022 and is an Atos BullSequana XH2000 system. It consists mainly of three node types: 1) CPU Compute nodes with AMD EPYC processors in different main memory configurations, 2) GPU nodes with NVIDIA A100 GPUs, and 3) FPGA nodes with Xilinx Alveo U280 and Intel Stratix 10 FPGA cards. While CPUs and GPUs are known off-the-shelf components in HPC systems, the operation of a large number of FPGA cards from different vendors and a dedicated FPGA-to-FPGA network are unique characteristics of Noctua 2. This paper describes in detail the overall setup of Noctua 2 and gives insights into the operation of the cluster from a hardware, software and facility perspective.
Keywords: Noctua 2; Supercomputer; FPGA; PC2; Paderborn Center for Parallel Computing

Visual Tracking Nonlinear Model Predictive Control Method for Autonomous Wind Turbine Inspection - Amer, Abdelhakim; Mehndiratta, Mohit; le Fevre Sejersen, Jonas; Pham, Huy Xuan; Kayacan, Erdal (2023 21st International Conference on Advanced Robotics (ICAR))

Analysis and Simulation of a Photonic Multiband FMCW Radar Sensor System using Nyquist Pulses - Kruse, Stephan; Schwabe, Tobias; Kneuper, Pascal; Kurz, Heiko G.; Meinecke, March-Michael; Scheytt, Christoph (German Microwave Conference (GeMiC))

Phase Noise Analysis of Photonic Radar Systems with Optical LO Distribution - Kruse, Stephan; Kneuper, Pascal; Schwabe, Tobias; Kurz, Heiko G.; Meinecke, Marc-Michael; Gonzalez-Huici, María A.; Scheytt, J. Christoph (nternational Conference on Microwaves for Intelligent Mobility (ICMIM))

Doppler Analysis of a Lidar-Photonic Radar Combined Sensor System - Kruse, Stephan; Brockmeier, Jan; Kneuper, Pascal; Schwabe, Tobias; Kurz, Heiko G.; Meinecke, Marc Michael; Scheytt, J. Christoph (International Radar Symposium (IRS))

Inverses Verfahren zur Identifikation piezoelektrischer Materialparameter unterstützt durch neuronale Netze - Koch, Kevin; Claes, Leander; Jurgelucks, Benjamin; Meihost, Lars; Henning, Bernd (Fortschritte der Akustik - DAGA 2024)

Einfluss der periodischen Struktur auf geführte Wellen in gewebeverstärkten Polymeren - Claes, Leander (Fortschritte der Akustik - DAGA 2024)

Beschreibung des akustischen Verhaltens verklebter plattenförmiger Strukturen mittels Kopplungsmodellen - Zeipert, Henning; Hölscher, Jonas; Claes, Leander; Henning, Bernd (Fortschritte der Akustik - DAGA 2024)

On the repulsion effect of coupled Lamb wave modes - Nicolai, Marcel; Bulling, Jannis; Lugovtsova, Yevgeniya; Zeipert, Henning; Prager, Jens; Henning, Bernd (Fortschritte der Akustik - DAGA 2024)

SootUp: A Redesign of the Soot Static Analysis Framework - Karakaya, Kadiray; Schott, Stefan; Klauke, Jonas; Bodden, Eric; Schmidt, Markus; Luo, Linghui; He, Dongjie (Tools and Algorithms for the Construction and Analysis of Systems)
Abstract Since its inception two decades ago, Soot has become one of the most widely used open-source static analysis frameworks. Over time it has been extended with the contributions of countless researchers. Yet, at the same time, the requirements for Soot have changed over the years and become increasingly at odds with some of the major design decisions that underlie it. In this work, we thus present SootUp , a complete reimplementation of Soot that seeks to fulfill these requirements with a novel design, while at the same time keeping elements that Soot users have grown accustomed to.

UNav-Sim: A Visually Realistic Underwater Robotics Simulator and Synthetic Data-Generation Framework - Amer, Abdelhakim; Álvarez-Tuñón, Olaya; Uğurlu, Halil İbrahim; Le Fevre Sejersen, Jonas; Brodskiy, Yury; Kayacan, Erdal (2023 21st International Conference on Advanced Robotics (ICAR))

Modellierungen außerinstitutioneller Aneignungsprozesse digital-materieller Interfaces und (musik-)pädagogische Anschlüsse - Neuhausen, Timo; Ahlers, Michael (Musik – Digitalisierung – Bildung)

“Der Draht ist gut, hält uns ab vom dummen Leben“. Ironisierung als kommunikativer Versuch des Umgangs mit Entwertungs- und Gewalterfahrungen durch jüdische Textproduzenten im Getto Litzmannstadt - Markewitz, Friedrich (Invective Discourse)
Immediately after the National Socialist seizure of power, a comprehen-sive social, legal and ultimately existential exclusion of Jewish people began. The disturbing perception of the break-up of previous understandings of the world was intensified against the background of the acts of annihilation by the National Socialists. Countering this in a communicative form became an often agonizing challenge for Jewish speakers, but also a necessary need. This paper will focus on a communicative phenomenon that has been little researched in linguistics so far: The use of irony to counter experiences of devaluation and violence. By eval-uating ironic utterances in textual communications of the Litzmannstadt ghetto, the criticism of elements of National Socialist ideology will be tentatively made understandable, as well as the experiences of violence within the ghetto.

Haus oder Schule? oder Haus und Schule? Zur kulturell-gesellschaftlichen Bedeutung der historischen Textsorte 'Schulprogramm' hinsichtlich der Konstitution, Festigung wie Abgrenzung des Erziehungssystems im 19. Jahrhundert - Markewitz, Friedrich (Textsorten in Sprach-, Kultur- und Sozialgeschichte)

Ironie - Markewitz, Friedrich
Ironie lässt sich als uneigentliches Kommunikationsmittel beschreiben, mit dem etwas anderes zum Ausdruck gebracht wird, als Sprecher*innen oder Schreiber*innen eigentlich meinen. Dies erfordert eine Differenzierung in Gesagtes und Gemeintes. Doch diese Differenzierung ist längst nicht immer eindeutig und so lebt Ironie von einer interpretatorischen Ambivalenz, ob eine Äußerung wörtlich oder ironisch zu verstehen ist. Aufgrund dieser Ambivalenz und ihrer kulturgeschichtlichen Entwicklung erscheint Ironie als ebenso faszinierendes wie komplexes Sprach-Phänomen. Die vorliegende Einführung gibt aus kulturlinguistischer Perspektive Einblicke in die verschiedenen Möglichkeiten der theoretischen Beschreibung, methodischen Erfassung sowie empirischen Analyse von Ironie. Dabei werden einerseits alltagssprachliche Formen ironischen Kommunizierens in den Blick genommen, andererseits Möglichkeiten des interdisziplinären Anschlusses, um Ironie als linguistisches sowie als kulturgeschichtliches Phänomen zugänglich zu machen.

"Der Zeitgeist" (1922/23). Expressionismus in Österreich zwischen Kunst- und Weltanschauung - Heise, Tillmann (Expressionismus)

Das ‚andere‘ Europa der Schriftsteller. Ideen, Netzwerke und Schreibweisen des antiliberalen Europa-Diskurses in Deutschland und Österreich (1918–1934) - Heise, Tillmann

Einführung in das Bürgerliche Recht

§ 78 (Kartellrechtliche Grenzen der stillen Gesellschaft) - Bartlitz, David (Münchener Handbuch des Gesellschaftsrechts)

§ 6 (Kartellrechtliche Grenzen der Kommanditgesellschaft) - Bartlitz, David (Münchener Handbuch des Gesellschaftsrechts)